BUFFALO PRODUCTION AND CONSTRAINTS IN BANGLADESH - M. Saadullah /; Mayakanan; Sabujbag (Journal of Animal and Plant Sciences, 2012)
Like other developing countries, systems of buffalo production vary widely in accordance with climate, soil and socio economic opportunities in Bangladesh. Buffaloes in Bangladesh can be classified into 2 categories : (I) indigenous buffaloes, found in the coastal areas and marshy land of the country, (ii) migrated buffaloes from India and Myanmar found in the sugar- cane producing belt. The migrated buffaloes from India and other areas and swamp types respectively are generally river types. of coastal areas and marshy land are swamp types. A number of crossbred between swamp and river are also found in the coastal area. Most of the farmers are rural small holders who have traditionally integrated their livestock with crop production and buffaloes are raised mainly to provide draught power in crop production. The feed resource base for these buffaloes are scavenging and consists of crop residues, household waste, tree fodder, roots and tuber, grain by-products and anything edible found in the immediate environment. The management practices adopted by buffalo raisers usually depends on the type of production in which they are involved. At the village level production is usually based on a small herd of mixed ages and sexes generally for draught and breeding purposes. In a semi-intensive production system, buffaloes are kept mainly for specific purposes, i.e., either for draught or for milk production. The low productivity is due to the genetic character of the breed and also poor quality nutrition. It is suggested that productivity of these buffaloes mainly depends on genetic improvement, good ration, good management and also climatic conditions of an area.
Keywords: NA